Frequency of Pneumoconiosis and Related Factors in Ceramic Workers Admitted between 2016 - 2018 to the Occupational Diseases Clinic of a University Hospital in Turkey - Seher Kurtul; Funda Kaya AK; Meral Turk (Iranian Journal of Health, Safety and Environment, 2021)
Accumulation of metals and dust may lead to pneumoconiosis in long-term workers in the ceramic industry. This study aimed to evaluate the prevalence of pneumoconiosis and the affecting individual, occupational, medical, and socioeconomic factors in ceramic industry workers admitted to the clinic of the occupational disease of a university hospital. This cross-sectional study evaluated the medical records of 216 ceramic workers admitted to the Occupational Diseases clinic of a university hospital in Turkey, between May 2016 and June 2018. The sociodemographic characteristics, detailed occupational history, physical examination findings, respiratory function test results, and radiological results (chest x-ray and/or High-Resolution Computed Tomography-HRCT) of the workers were documented. Chest x-rays were evaluated by two occupational disease specialists with ILO pneumoconiosis certification. According to gender, 213 patients were male and 3 female. Pneumoconiosis was detected in 34 (11.1%) of the patients, all were male. There was a statistically significant correlation between total time of dust exposure and pneumoconiosis diagnosis (p=0.002). In total, 80.6% of patients were asymptomatic at presentation to the clinic. According to the evaluation of the standard chest radiography of the cases, most of the opacities were characterized as p (120, 55.6%) or q (13, 6.0%) and observed in mid and upper zones; 10 patients showed s opacity (4.6%) and 1 patient showed r opacity (0.5%). Spirometry results of the cases who were categorized according to the results of ILO radiological assessment were compared and no statistically significant difference was found between the groups (p>0.05). When the HRCT results of 196 workers were evaluated, 142 cases (65.7%) were shown reticular opacity, 87 (40.3%) nodule, and 2 cases (0.9%) large opacity. These results emphasize the importance of conducting follow-up studies in workers exposed to respirable particles in the ceramic industry and reforming health policies related to pneumoconiosis.